Opsoclonus Myoclonus Presenting as Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Two cases of non-epileptic opsoclonus presenting as status epilepticus are reported fom the John Radcliffe Hospital, Oxford, UK.